Implementation of Public Service Policy in Handling Elec-tricity Customer Complaints: A Study at PT PLN Persero UP3 Samarinda - Edi Pamungkas; Sri Roekminiati; Sri Kamariyah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study analyzes the implementation of public service policy in handling electricity customer complaints at PT PLN (Persero) UP3 Samarinda and evaluates customer-perceived service quality. The research addresses the gap between formal complaint-handling policies and operational practice, reflected in increasing public complaints against state-owned enterprises, including PLN. A descriptive qualitative approach was applied through in-depth interviews, observation, and documentation involving 13 informants selected using purposive and snowball sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, with source triangulation to ensure validity. The study combines Edwards III’s policy implementation model, covering communication, resources, disposition, and bureaucratic structure, with the SERVQUAL model, covering tangibles, reliability, responsiveness, assurance, and empathy. Findings show that communication and disposition are satisfactory, while resources and bureaucratic structure require improvement due to an imbalanced customer service ratio and fragmented information systems. SERVQUAL results show negative gaps in all dimensions, especially responsiveness and reliability. The study concludes that complaint-handling policy implementation is adequate but needs stronger human resources, integrated real-time information systems, and improved customer digital literacy for more responsive and reliable public service.